Coated Sutures. Issue 3 (September 2015) - Beitzel, Knut; Voss, Andreas; McCarthy, Mary-Beth; Russell, Ryan P.; Apostolakos, John; Cote, Mark P.; Mazzocca, Augustus D.
Abstract : The addition of specific proteins or growth factors onto sutures would provide a direct application of exogenous factors to promote tissue repair. The higher levels of growth factors and cytokines may optimize the healing environment and promote tissue recovery. Despite this proposed benefit, the current orthopedic literature on the use of coated sutures is limited. Although several of the published studies investigating healing improvement by coated sutures have shown promising results, these data are only based on in vitro or small animal experiments. Recent meta-analyses have reported positive effects of triclosan-coated antimicrobial sutures in regards to reduction of surgical site complications. However, biologically coated sutures are not yet widely accepted due to several unanswered questions (concentration, release kinematics, tissue reactions, etc.) in addition to the high costs of such products. Further studies are needed to demonstrate the efficacy of coated sutures in orthopedic surgery.